Postglacial environmental changes at the eastern Laptev Sea continental margin: evidence from benthic and planktic foraminiferal assemblages - Chistyakova, Natalia; Taldenkova, Ekaterina; Ovsepyan, Yaroslav; Spielhagen, Robert (University of Oulu and Thule Institute, 2012)
In order to reconstruct the late glacial to Holocene history of Atlantic-derived water (ADW) inflow into the Arctic Ocean along the northern Eurasian margin, past freshwater inputs and variability in sea-ice extent we carry out investigation of the distribution and abundance of benthic and planktic foraminifers in the AMS14C-dated sediment core PS2458-4 from the eastern Laptev Sea continental slope (78°10.0’N, 133°23.9’E) located at 983 m water depth in front of the position of the former Lena and Yana river mouths on the shelf break (Spielhagen et al., 2005). The 822 cm long sediment sequence was sampled continuously in 2 cm thick slices. The core is well-dated from 201 cm down to 625 cm, this sediment interval corresponds in time to 8.9-14.6 cal.ka (Spielhagen et al., 2005), whereas the basal and uppermost parts of the core lack sufficient amount of datable material. Based on preliminary data on taxonomic composition and abundance of benthic and planktic foraminifers several intervals were distinguished corresponding to certain changes in past environments. The oldest lateglacial period (822-660 cm) is characterized by very low abundance of microfossils suggesting harsh environmental conditions with heavy sea-ice cover. However, high percentages of ADW-indicative benthic foraminifer Cassidulina neoteretis and the presence of diverse planktic subpolar species give evidence for the strong subsurface inflow of ADW along the Laptev Sea continental slope. The increasing representation of Elphidium clavatum, higher foraminiferal abundance and species diversity imply growing fluvial influence during early deglaciation (660-600 cm, until 14.2 cal.ka). The abundance of subpolar planktic foraminifers is the highest although their diversity considerably decreases compared with the earlier lateglacial times. Enhanced ADW inflow to the core site is manifested by the sharp dominance of C. neoteretis in the record during the Bølling-Allerød period (600-520 cm, 14.2-12.9 cal.ka). Transition to the Younger Dryas period ...